PERTANGGUNGJAWABAN PELAKU PIDANA PORNOAKSI YANG VIDEONYA DISEBARKAN OLEH ORANG LAIN - Reni Marbun; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Pornography is not just worrying and tarnishing the good name and detrimental to the honor of others and very degrading surrounding. Besides that, talking about the crime of porno-action in the mass media at the moment is inseparable from criminal liability against the spread of porn-action which results in the ease of people being able to access internet sites. Therefore it is necessary to examine the problem in this study is how is the criminal responsibility of the perpetrators of pornography whose videos are spread by others, and whether the perpetrators of pornography spreaders can be accounted for by criminal law.This research is a normative legal research, in which this normative legal research is carried out by examining library materials or secondary data consisting of primary, secondary and tertiary legal material, which examines the legal principles contained in the Criminal Law Code. This study uses descriptive research, because the author intends to provide a clear and detailed description of the Criminal Liability of Porno Actors whose Video is distributed by others.From the results of the study, it was concluded that the criminal liability of pornography perpetrators whose videos were distributed by others has not been carried out to the maximum extent possible by law enforcement officials because regulations related to criminal acts are very weak because they have not been well socialized and comprehensive, and viewed from the point of view of law enforcement officials who do not understand all the current regulations so that they have not been carried out out of the three rules, namely the Criminal Code, Law Number 44 Year 2008 Regarding Pornography and Law Number 19 Year 2016 Amendment to Law Number 11 of 2008 concerning Transaction and Electronic Information.Keywords: Invistigation-People Smuggling- suspect